ChemInform Abstract: Rhodium(II)‐Catalyzed Cycloaddition Reactions of Non‐classical 1, 5‐Dipoles for the Formation of Eight‐Membered Heterocycles. Issue 11 (February 2016) - Lee, Dong Jin; Ko, Donguk; Yoo, Eun Jeong
Abstract: A new type of [5 + 3] cycloaddition between pyridinium zwitterion 1, 5‐dipole equivalents and enol diazoacetates is developed for the synthesis of eight‐membered heterocycles.